Ethnicity as a risk factor for gambling disorder: a large-scale study linking data from the Norwegian patient registry with the Norwegian social insurance database - Sarah Helene Aarestad; Eilin Kristine Erevik; Otto Robert Frans Smith; Mark D. Griffiths; Tony Mathias Leino; Rune Aune Mentzoni; Ståle Pallesen (BMC Psychology, 2023)
Abstract Background The study investigated ethnicity as a risk factor for gambling disorder (GD), controlling for demographics, citizenship, and years of residency in Norway. Methods The sample comprised 65,771 individuals from a national patient registry (n = 35,607, age range 18–88 years) and a national social insurance database in Norway (n = 30,164, age rage 18–98 years). The data covered the period from 2008 to 2018. Results The results showed that when controlling for age and sex, ethnic minorities were overall less likely than those born in Norway to be diagnosed with GD (odds ratio [OR] ranging from 0.293 to 0.698). After controlling for citizenship and years of residency in Norway, the results were reversed and indicated that ethnic minorities were overall more likely to be diagnosed with GD (OR ranging from 1.179 to 3.208). Conclusion The results suggest that citizenship and years of residency are important variables to account for when assessing the relationship between ethnicity and being diagnosed with GD. Our results may be explained by people from ethnic minority groups being more likely to experience gambling problems but less likely to seek contact with healthcare services for gambling problems.